2013
DOI: 10.1017/s0025315413001173
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopy of the cypris larvae ofCapitulum mitella(Cirripedia: Thoracica: Scalpellomorpha)

Abstract: Adult specimens ofCapitulum mitellawere collected in August 2011 in the intertidal zone of Dinghai, Fuzhou, Fujian, China (26°16′N 119°48′E). The morphology of the cypris larva reared under our conditions was determined using scanning electron microscopy (SEM). Special emphasis was given to the carapace, lattice organs, antennules, thoracopods and furcal rami. The whole carapace surface is sculptured by slender ridges demarcating rectangular or irregular polygonal areas with very fine pores. The cyprid possess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…When they first appear, the primordia of the paired scutal and tergal plates are always irregularly polygonal-shaped. The developing hermaphrodite body does not yet fill out the space enclosed by the cypris carapace ( Fig 5A and 5B ), and, in agreement with [ 34 ], has not started to expand in length to any significant degree ( Fig 2B ). Anteriorly, cells in the future peduncle region begin to compact, and the first signs of a constriction between peduncle and capitulum become visible (Figs 2B and 5A ).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…When they first appear, the primordia of the paired scutal and tergal plates are always irregularly polygonal-shaped. The developing hermaphrodite body does not yet fill out the space enclosed by the cypris carapace ( Fig 5A and 5B ), and, in agreement with [ 34 ], has not started to expand in length to any significant degree ( Fig 2B ). Anteriorly, cells in the future peduncle region begin to compact, and the first signs of a constriction between peduncle and capitulum become visible (Figs 2B and 5A ).…”
Section: Resultssupporting
confidence: 85%
“…Subsequent studies by Takenaka [ 31 ] and Glenner and Høeg [ 32 , 33 ] elaborated further on the development of single organs and structures. While Høeg et al [ 21 ] provided detailed knowledge on the cypris metamorphosis, information on cypris metamorphosis still only exists for a handful of species [ 34 , 35 , 36 ]. Moreover, none of these studies concern the post-settlement development of dwarf males in thoracican barnacles and very few studies offer a comparative study on the morphology and evolution of dwarf male morphology in androdioecious species [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, our analysis and previous studies show that there is significant variation in cypris antennular structure among cirripedes. This includes both the specific array of setae and the shape and detailed structure of the attachment organ, but the extent to which this structural variation is correlated with differences in habitat and settlement remains somewhat uncertain (Glenner et al, 1989;Glenner and Høeg, 1995;Moyse et al, 1995;Blomsterberg et al, 2004, Kolbasov andHøeg, 2007;Brickner and Høeg, 2010;Chen et al, 2013;Rao and Lin, 2014;Al-Yahya et al, 2016). Nevertheless, the present analysis and the results in Al-Yahya et al (2016) clearly show that species from coastal hard-bottom habitats have a unique and almost identical antennular structure.…”
Section: Discussionmentioning
confidence: 62%
“…In their study comprising species from a wide range of taxa and habitats, Al-Yahya et al (2016) suggested that a shoe-shaped third segment surrounded by a skirt is associated with an epibiotic habitat, while a bell-shaped segment surrounded by a velum is associated with a hard-bottom habitat; but their statistical analysis failed to adequately support this claim. It is nevertheless striking that a bell-shaped third segment has only been found in cyprids from hard-bottom balanomorphans and in the very few pedunculated barnacles from this same habitat, namely, Pollicipes pollicipes and Capitulum mitella (Moyse et al, 1995;Rao and Lin, 2014;Al-Yahya et al, 2016). This suggests that this segment shape is indeed associated with hard bottoms; but a detailed morphometric analysis, as in the present paper, that also includes P. pollicipes, C. mitella, and some of the numerous hard-bottom-inhabiting species from the balanomorphan superfamilies Chthamaloidea and Corunuloidea, is needed to further substantiate this claim.…”
Section: Discussionmentioning
confidence: 99%
“…The C. mitella cyprid morphology has been described in detail (Rao & Lin, 2014) and cyprids have been successfully induced to metamorphose into juvenile barnacles after artificial exposure to juvenile hormone III (JH- III) (Lin & Rao, 2017). Nevertheless, the effects of various factors on settlement remain unknown.…”
Section: Introductionmentioning
confidence: 99%